1991
DOI: 10.1021/np50077a017
|View full text |Cite
|
Sign up to set email alerts
|

9β-Lanostane-Type Triterpene Lactones from the Stem Bark of Abies veitchii

Abstract: Two new tetracyclic triterpene lactones were isolated, together with two known compounds, 3-oxo-93-lanosta-7,24-dien-26,23R-olide [2] and 3ß-1^ ^-9ßlanosta-7,24-dien-26,23R-olide [31, from the stem bark of Abies veitchii. The structures of the new compounds were established as 3ot-hydroxy-9ß-lanosta-7,24-dien-26,23f?-olide [6] and 3ce-methoxylanosta-7,9( 1 l),24-trien-26,23R-olide [7], respectively, on the basis of chemical and spectral evidence.Abies veitchii Lindl. (Pinaceae) (Japanese name: Shirabiso) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…The UV and IR spectra showed absorption bands for a hydroxy group (n max 3445 cm ±1 ), six-membered ring ketone (n max 1718 cm ±1 ), transoid ene-dione (l max 262 nm, n max 1679 cm ±1 ) and a,b-unsaturated-g-lactone ring (n max 1752 cm ±1 ). (s)] which was closely similar to those of abieslactone and its analogues (9), (10). In the EI-MS spectrum (Fig.…”
Section: Resultssupporting
confidence: 72%
“…The UV and IR spectra showed absorption bands for a hydroxy group (n max 3445 cm ±1 ), six-membered ring ketone (n max 1718 cm ±1 ), transoid ene-dione (l max 262 nm, n max 1679 cm ±1 ) and a,b-unsaturated-g-lactone ring (n max 1752 cm ±1 ). (s)] which was closely similar to those of abieslactone and its analogues (9), (10). In the EI-MS spectrum (Fig.…”
Section: Resultssupporting
confidence: 72%
“…CC of fraction (C) with chloroform : methanol (99 : 1) yielded oleanolic acid and ursolic acid which were identified by comparing their 1 H NMR, 13 C NMR and mass spectra data with those available in the literature (Mahato and Kundu, 1994;Budzikiewicz et al, 1963). Comparison of 1 H and 13 CNMR of 3-epiursolic acid and 3-epioleanolic acid with their corresponding stereoisomers ursolic acid and oleanolic acid respectively clearly indicated that the only difference in the configuration was at the C-3 position between the isomers (Tanaka and Matsunaga, 1991). The appearance of a broad singlet (d 3.45; in acetate at d 4.67) in 1 H NMR and a slightly upfield 13 C signal at d 76.5 indicated a b hydrogen (a-OH) at the 3 position in 3-epiursolic acid and 3-epioleanolic acid.…”
Section: Methodsmentioning
confidence: 94%
“…3) established its absolute configuration as (17S,23S)-17, 23-epoxy-3,7-dioxo-8,24-lanostadien-26,23-olide. Compound 4 was assigned the molecular formula of C 30 H 46 O 3 from the HRESIMS at m/z 455.3527 [M+H] + . The 1 H and 13 C NMR spectroscopic data resembled that for (23R)-3a-hydroxy-9b-lanosta-7,24-dien-26,23-olide (15) (Tanaka and Matsunaga, 1991), with the main difference being that the olefinic signal at d C 121.6 (C-7) in 15 was shifted to d C 114.4 in 4. In the HMBC spectrum, Me-19 was correlated to d C 148.6, while Me-30 was correlated to d C 41.8.…”
Section: Resultsmentioning
confidence: 60%